Validation of 24‐h dietary recall for estimating nutrient intakes and adequacy in adolescents in Burkina Faso - Arsenault, Joanne E.; Moursi, Mourad; Olney, Deanna K.; Becquey, Elodie; Ganaba, Rasmané; Pedehombga, Abdoulaye; Anick Ouattara; Sosthene Kere (John Wiley & Sons, 2020)
Data on dietary nutrient intakes of adolescents in low‐ and middle‐income countries (LMIC) is lacking partly due to the absence of validation studies of the 24‐h recall method in adolescents. We conducted a validation study of 24‐h recall (24HR) compared with observed weighed records (OWR) in adolescents (n = 132, 10–11 years; n = 105, 12–14 years). Dietary data were collected for the same day by both methods by conducting the 24HR the day after the OWR. For OWR, all foods consumed by adolescents from the first to last meal of the day were weighed; for 24HR adolescents reported foods consumed using portion aids. Food intakes were converted to nutrients. Nutrient intakes by both methods were tested for equivalence by comparing the ratios (24HR/OWR) with equivalence margins of within ±10%, 15% and 20% of the ratio. Prevalences of inadequacy (POIs) were obtained using the NCI method. Mean ratios for energy were 0.88 and 0.92, for younger and older adolescents, respectively, and other nutrients ranged between 0.84 and 1.02. Energy intakes were equivalent within the 15% bound, and most nutrients fell within the 20% bound. POI was overestimated by 24HR, but differences were less than 25 percentage points for most nutrients. Half of adolescents omitted foods in recalls, mainly sweet or savoury snacks, fruits and beverages. Our study showed that adolescents underestimated intakes by 24HR; however, the degree of underestimation was generally acceptable for 12–14‐year‐olds within a bound of 15%. Errors could possibly be reduced with further training and targeted probing.